Numerical investigation of nanoparticle deposition location and pattern on a sharp-bent tube wall. (January 2021) - Kwak, Dong-Bin; Kim, Seong Chan; Lee, Handol; Pui, David Y.H.
Highlights: Modified single-particle tracking method based on aerosol mass flow rate was employed. The highest LDEF on a sharp-bent tube were observed right after the bending region for all different conditions. At low Re, most of particles were deposited at the outer wall. At high Re, particles were uniformly deposited along the azimuthal angles due to its strong secondary flow. Abstract: The characteristics of fluid flow on a sharp-bent tube under various conditions were analyzed. Numerical simulations for analyzing the particle deposition locations and patterns on a sharp-bent tube were conducted by using the modified single-particle tracking analysis based on aerosol mass flow rate. Through the numerical calculation, we showed that after the bending point in a sharp-bent tube, the faster axial velocity occurred near the outer wall, and the boundary layer at high Reynolds number became thinner. Furthermore, the faster radial velocity near the tube wall was observed at less developed-flow region at high Reynolds number owing to the stronger secondary flow. The nanoparticle deposition locations and patterns were systematically examined in various viewpoints including cumulative number of deposited particles, local deposition enhancement factor, and particle deposition pattern according to azimuthal angles. We found that most of the nanoparticles were deposited on the outer wall right after the bending point owing to outward-sloping flow. Moreover, the difference in relative deposition efficiency along the azimuthal angles at each section in the sharp-bent tube was reduced as Reynolds number increased. This is because the nanoparticles near the wall were well mixed due to the strong secondary flow at high Reynolds number. Graphical abstract: Image, graphical abstract